The effect of structural changes on the functional properties of Fe65.5Cr4Mo4Ga4P12C5B5.5 bulk metallic glass - Mitrović Nebojša; Čukić Bratislav; Nedeljković Borivoje; Kalezić-Glišović Aleksandra; Obradović Nina (Serbian Journal of Electrical Engineering, 2024)
The ferromagnetic Fe65.5Cr4Mo4Ga4P12C5B5.5 bulk metallic glass rods of 1.8 mm diameter were prepared prepared by the copper-mold casting technique. As-quenched and successive furnace annealed samples were examined by thermal analysis (DTA), X-ray diffraction (XRD), thermomagnetic, coercivity, and hardness measurements. The wide supercooled liquid region DTx of 57 K and reduced glass transition temperature Trg of 0.57 indicate enhanced glass forming ability and high thermal stability against crystallization. After the third annealing at 673 K the most intensive stress relief is followed by an increase in the magnetic permeability of 23%, an increase in the Curie temperature (to 558 K), and an improvement in coercivity of about 40%. Coercivity abruptly increases after thermal treatment at 773 K, indicating the presence of crystalline inclusions that hinder stress relief. The XRD pattern of the rod annealed at 873 К shows several intermetallic compounds formed by crystallizing the amorphous phase, such as B48B2C2, and iron-based compounds Fe2Мо4C and Fe3B. The rods were explored for the increase in hardness which evolved due to stress relief and after transformation from the amorphous into crystalline phase.